2014
DOI: 10.1007/s10479-014-1687-2
|View full text |Cite
|
Sign up to set email alerts
|

Workforce scheduling and routing problems: literature survey and computational study

Abstract: In the context of workforce scheduling, there are many scenarios in which personnel must carry out tasks at different locations hence requiring some form of transportation. Examples of these type of scenarios include nurses visiting patients at home, technicians carrying out repairs at customers' locations and security guards performing rounds at different premises, etc. We refer to these scenarios as Workforce Scheduling and Routing Problems (WSRP) as they usually involve the scheduling of personnel combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 138 publications
(84 citation statements)
references
References 43 publications
0
82
0
2
Order By: Relevance
“…The existence of connected activities gives raise to time-dependent activities constraints. A study by Castillo-salazar et al [8] applied a mixed integer programming (MIP) solver to tackle WSRP with time-dependent activities constraints. That study revealed that tackling instances with 50 activities or more required considerable computational time.…”
Section: Related Workmentioning
confidence: 99%
“…The existence of connected activities gives raise to time-dependent activities constraints. A study by Castillo-salazar et al [8] applied a mixed integer programming (MIP) solver to tackle WSRP with time-dependent activities constraints. That study revealed that tackling instances with 50 activities or more required considerable computational time.…”
Section: Related Workmentioning
confidence: 99%
“…A solution requires all visits to be served hence it is not always possible to meet all visit requirements and workers availability. To evaluate the quality of a solution, the tier-based minimisation objective function shown in Equation (1) is utilised, which is employed by our industrial partner and also commonly used in the literature [16,2].…”
Section: The Workforce Scheduling and Routing Problemmentioning
confidence: 99%
“…Solving this problem requires defining a schedule and a route plan for each worker such that all tasks (where possible) are covered. These problems combine features from both scheduling and routing problems, making them very challenging optimisation problems [1][2][3]. Examples of practical applications of WSRP are home healthcare scheduling [4,5], technician scheduling [6,7] and security personnel scheduling [8].…”
Section: Introductionmentioning
confidence: 99%
“…Common constraints (see also (Castillo-Salazar et al, 2014)) such as path constraint (2), skill and qualification (7) and time windows (9) form the basic structure of the scheduling and routing problem (Dantzig and Ramser, 1959;Bredstrom and Ronnqvist, 2008;Dohn et al, 2009;Castro-Gutierrez et al, 2011;Rasmussen et al, 2012). Tailor cut constraints adopted from literature are the availability constraints (10,11) while the constraints that required further adaptation to our problem features are the working region (13) (implemented as soft constraint) and startend paths (3-6).…”
Section: Problem Description and Formulationmentioning
confidence: 99%
“…(Castillo-Salazar et al, 2014). One specific example of WSRP is home health care services where nurses or care workers should deliver care services at the patient's home.…”
Section: Introductionmentioning
confidence: 99%